Comprehensive Analysis of the PRDXs Family in Head and Neck Squamous Cell Carcinoma - Cao, Ruoyan; Zhang, Weilin; Zhang, Hongjian; Wang, Lixuan; Chen, Xijuan; Ren, Xianyue; Cheng, Bin; Xia, Juan (Frontiers in Oncology, 2022)
The peroxidase family of peroxiredoxins (PRDXs) plays a vital role in maintaining the intracellular balance of ROS. However, their function in head and neck squamous cell carcinoma (HNSCC) has not been investigated. We therefore explored the value of PRDXs in HNSCC. We found that the expression of PRDX1, PRDX4, and PRDX5 in HNSCC increased while the expression of PRDX2 decreased. Moreover, the high expression of PRDX4/5/6 indicated a poor prognosis. Lower expression of PRDX1/5 was linked to more immune cell infiltration, higher expression of immune-related molecules and a more likely response to anti-PD-1 treatment. Moreover, PRDX5 knockdown inhibit HNSCC cell proliferation, invasion and metastasis and it might promote apoptosis through its antioxidant property. Taken together, our study highlights the potential role of PRDXs in HNSCC. The function of PRDX5 in the development of HNSCC and the formation of the immune microenvironment makes it a promising potential therapeutic target.